ANALYSIS OF INSTRUMENT TEST OF HISTORICAL THINKING SKILLS IN SENIOR HIGH SCHOOL HISTORY LEARNING WITH QUEST PROGRAMS - Ofianto, Ofianto (Jurusan Sejarah Universitas Negeri Semarang, Semarang, 2018)
This research is descriptive quantitative research and aimed to described quality of questions history subject in West Sumatra District including validity, item difficulty, item discrimination, distractor efficiency and reliability. Objects in this study are questions test and 443 sheets of answer sheet including MAN 3 Padang, MAN Pariaman and MAN 3 Padang Panjang, key answer test, a test blue print and then it?s analysis with quest program. The result of this research shows that the content validity have category of valid was 28 questions (56%) and un-valid was 22 questions (44%). Item difficulty questions are easy category was 1 question (2%), immediate category was 9 questions (18%) and difficult category was 40 questions (80%). Item discrimination is weak category was 26 questions (52%), enough category was 18 questions (36%), good category was 4 questions (8%), very good questions was 1 question (2%) and bad category was 1 question (2%). Distractor efficiency was 47 questions (94%) and not function was 3 questions (6%). The average Kuder-Richarson formula 20 reability coefficient was 0,53 means it has enough reliability. Key words: historical thinking; validity; item difficulty; item discrimination; distractor of efficiency; reliability